Application of membrane bioreactor for sulfamethazine-contained wastewater treatment. (February 2018) - Shi, Bing-Jing; Wang, Yunkun; Geng, Yi-Kun; Liu, Ru-Dong; Pan, Xin-Rong; Li, Wen-Wei; Sheng, Guo-Ping
Abstract: The presence of antibiotics in wastewater has been widely confirmed. Membrane bioreactor (MBR), as an efficient wastewater treatment technology, has attracted increasing interest in its ability to remove antibiotics in recent years. However, its long-term operation stability and the underlying mechanisms for antibiotics removal are still poorly understood. In this study, a hollow fiber MBR was used to treat low concentration sulfamethazine (SMZ) contained wastewater. The long-term effects of various SMZ concentrations on nutrients removal, SMZ degradation, and sludge characteristics were investigated. During the 244 days operation, the overall SMZ removal efficiency could reach 95.4 ± 4.5% under various SMZ concentrations and hydraulic retention times. The reactor exhibited high chemical oxygen demand and NH4 + -N removal efficiencies, which reached 93.0% and 96.2%, respectively. A sludge concentration of 4.1 ± 0.3 g/L was maintained in the system without excess sludge discharge. The dosage of SMZ had obvious effect on sludge characteristics. The contents of extracellular polymeric substances (EPS) in MBR decreased after a long-term operation of the reactor under SMZ pressure. The low sludge concentration and the reduced EPS content were also beneficial for mitigating membrane fouling. Thus, this study provides a low-cost, efficient and simple approach to treat SMZ-contained wastewater. Highlights: A MBR was used to treat low concentration sulfamethazine contained wastewater. The underlying mechanisms for SMZ removal was investigated. The MBR system showed a good performance for SMZ removal. The membrane fouling was reduced in this MBR.